Targeting histone deacetylase 8 as a therapeutic approach to cancer and neurodegenerative diseases - Chakrabarti, Alokta; Witt, Olaf (Future medicinal chemistry, 2016)
Histone deacetylase 8 (HDAC8), a unique class I zinc-dependent HDAC, is an emerging target in cancer and other diseases. Its substrate repertoire extends beyond histones to many nonhistone proteins. Besides being a deacetylase, HDAC8 also mediates signaling via scaffolding functions. Aberrant expression or deregulated interactions with transcription factors are critical in HDAC8-dependent cancers. Many potent HDAC8-selective inhibitors with cellular activity and anticancer effects have been reported. We present HDAC8 as a druggable target and discuss inhibitors of different chemical scaffolds with cellular effects. Furthermore, we review HDAC8 activators that revert activity of mutant enzymes. Isotype-selective HDAC8 targeting in patients with HDAC8-relevant cancers is challenging, however, is promising to avoid adverse side effects as observed with pan-HDAC inhibitors.